2023
DOI: 10.36628/ijhf.2022.0032
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Modification in Heart Failure Management: Are We Using Evidence-Based Recommendations in Real World Practice?

Abstract: The heart failure (HF) guideline’s purpose is to assist medical professionals while treating patients with HF in accordance with the best current research. Many cases of HF are both, avoidable and treatable thanks to scientific trials. Management is, therefore, based on lifestyle changes, also called non-pharmacological treatment. These, based on lifestyle changes, should be recommended in every patient at risk for HF or with diagnosed of HF, but evidence in itself is scarce. DASH Diet could be clearly benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Of note, these pathologies are characterized by the presence of low-grade systemic inflammation, oxidative stress, dysregulation of the neuro-hormonal system and metabolic dysfunction settling the basis for maladaptive cardiac remodeling and impaired function, and/or resulting in individual’s multisystem dysregulations, depletion of physical, cognitive reserve, and poor tolerance to stress, substantially leading to the development of frailty and HFpEF. 72 73 74) …”
Section: Elderly Hfpef and Frailty Profilementioning
confidence: 99%
“…Of note, these pathologies are characterized by the presence of low-grade systemic inflammation, oxidative stress, dysregulation of the neuro-hormonal system and metabolic dysfunction settling the basis for maladaptive cardiac remodeling and impaired function, and/or resulting in individual’s multisystem dysregulations, depletion of physical, cognitive reserve, and poor tolerance to stress, substantially leading to the development of frailty and HFpEF. 72 73 74) …”
Section: Elderly Hfpef and Frailty Profilementioning
confidence: 99%
“…Only a small pilot study reported that a fluid restriction group experienced fewer typical HF symptoms, greater thirst distress, and stable heart-related quality of life [ 83 ]. To further investigate the effects of fluid restriction in HF patients, a planned RCT called Fluid REStriction in HF vs. liberal fluid UPtake (FRESH-UP) aims to determine whether fluid restriction to < 1.5 L contributes to symptom improvement in New York Heart Association class II or III symptomatic HF patients [ 81 , 84 ].…”
Section: Diet and Lifestyle Modificationmentioning
confidence: 99%
“…The 2021 European Society of Cardiology guidelines discourage the consumption of > 5 g of salt per day to help manage HF. While there is a consensus on avoiding excessive salt intake, the evidence regarding the benefits of strict salt restriction (< 2 g/d) for reducing death or hospitalization in HF patients is not consistent [80][81][82]. In fact, one RCT showed that a group consuming 2-3 g of salt per day had a numerically lower risk of death compared to one consuming < 2 g [80].…”
Section: Salt Intake and Fluid Restrictionmentioning
confidence: 99%
“…Lifestyle changes also can help manage CHF and improve quality of life. These changes include losing weight (if needed), physical activity/exercise, consuming less sodium (salt), managing substance abuse, and managing stress levels (2,3).…”
Section: Introductionmentioning
confidence: 99%